2009
DOI: 10.1088/0031-9155/55/1/012
|View full text |Cite
|
Sign up to set email alerts
|

Implementation and evaluation of various demons deformable image registration algorithms on a GPU

Abstract: Online adaptive radiation therapy (ART) promises the ability to deliver an 20 optimal treatment in response to daily patient anatomic variation. A major technical barrier for the clinical implementation of online ART is the requirement of rapid image segmentation. Deformable image registration (DIR) has been used as an automated segmentation method to transfer tumor/organ contours from the planning image to daily images. However, the current 25 computational time of DIR is insufficient for online ART. In this … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
199
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 228 publications
(200 citation statements)
references
References 33 publications
1
199
0
Order By: Relevance
“…Demons is a process of optimizing the displacement of every pixel in the floating image to accurately construct point-to-point correspondence of the registered images, which can be mathematically represented by two terms of a similarity measurement and regularization of DVF: (2) where transforms the points of the moving image into the coordinate of the fixed image by the spatial transformation ; accounts for the noise on the image intensity; and controls the amount of necessary regularization. An image similarity term measures the similarity of the two registered images.…”
Section: Prior Delineation Of Ct Based Dir Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Demons is a process of optimizing the displacement of every pixel in the floating image to accurately construct point-to-point correspondence of the registered images, which can be mathematically represented by two terms of a similarity measurement and regularization of DVF: (2) where transforms the points of the moving image into the coordinate of the fixed image by the spatial transformation ; accounts for the noise on the image intensity; and controls the amount of necessary regularization. An image similarity term measures the similarity of the two registered images.…”
Section: Prior Delineation Of Ct Based Dir Methodsmentioning
confidence: 99%
“…investigated four ITK based Demons variant algorithms and found that the performance of the symmetric Demons implemented by Vercautern [2] was advantageous over the original Demons and the other two Demons variants. The symmetric Demons defines the displacement field as follows: (1) where and respectively represent the moving image after the ith iteration and the fixed image; and denote the gradient image; and is the mean-squared value of the image voxel size.…”
Section: S1038mentioning
confidence: 99%
“…Li et al 38 developed a 3D lung tumor localization method based on principal component analysis (PCA), where the accuracy of the tracking algorithm is limited by the accuracy of training deformable vector field derived using the demons algorithm. 44 Lewis et al 42, 43 developed a phase-binned tumor trajectory reconstruction method. The method can only provide one representative phase-binned tumor trajectory from a CBCT scan, however, with the aid of a breathing signal provided by an additional device.…”
Section: Introductionmentioning
confidence: 99%
“…Many authors are focusing their efforts in how to adapt the implementation of numerical methods under the CUDA compliance. Some examples can be found in literature for different topics such as physics 7,8 , astronomy 9, 10 , images [11][12][13] , biomedical applications 14,15 and computer science 16 . The acceleration of the SF-FDTD by means of GPU computing has been recently introduced by Shahmansouri 17 et al In their work GPU computing is applied to accelerate the SF-FDTD implementation for Drude-Lorentz dispersive media.…”
Section: Introductionmentioning
confidence: 99%